2000
DOI: 10.1080/01919510009408801
|View full text |Cite
|
Sign up to set email alerts
|

Selective Removal of Lipophilic Wood Extractives from Paper Mill Water Circulations by Ozonation

Abstract: Printed in the U.S.A. 0191-951m63.00+ .a) lntcrnntiond Ozone Assmintion AbstractCirculation waters from paper mills and TMP production were treated by selective ozonation to remove lipophilic wood extractives (LWE's). In the reaction model, ozone was assumed to react with overall organic matter measured as COD with one global reaction rate coefficient. The target compounds, LIVE'S, are a part of the overall organic matter and they react with ozone with a specific reaction rate coefficient. Reaction selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In addition, the ozone oxidation of resin acids has also been addressed relatively effective Laari et al 2000;Ledakowicz et al 2006;Roy-Arcand and Archibald 1996); whereas starch oxidation products showed lower degradation rates than lignin derivatives ones, probably due to the absence of carboncarbon double bonds (Amat et al 2005b;Langlais et al 1991) (Figure 1). Furthermore, why p-toluenesulfonic acid showed a slower degradation rate than other lignin derivatives was explained by the strong deactivating effect of its sulfonic group (Amat et al 2004).…”
Section: Ozone Oxidation Processesmentioning
confidence: 99%
“…In addition, the ozone oxidation of resin acids has also been addressed relatively effective Laari et al 2000;Ledakowicz et al 2006;Roy-Arcand and Archibald 1996); whereas starch oxidation products showed lower degradation rates than lignin derivatives ones, probably due to the absence of carboncarbon double bonds (Amat et al 2005b;Langlais et al 1991) (Figure 1). Furthermore, why p-toluenesulfonic acid showed a slower degradation rate than other lignin derivatives was explained by the strong deactivating effect of its sulfonic group (Amat et al 2004).…”
Section: Ozone Oxidation Processesmentioning
confidence: 99%
“…Also, when water circulations are closed these compounds are accumulated in the process waters leading to problems in process operation and in product quality. Ozonation was used to remove the LWEs in circulation waters from paper mills and TMP production and it was found that the high ozone dose of about 100-300 mg/dm 3 was needed for removal of 50% extractives [17]. The reason is the high concentration of organic matter in the waters leading to excessive usage of ozone despite the high selectivity of the reaction.…”
Section: Ozonation Of Pollutants Commonly Found In Pulp Mill Effluentmentioning
confidence: 99%
“…Decomposition of toxic contaminants was carried out firstly by ozonation to reduce the toxicity of initial organic matter. This fact was justified because ozone promoted the formation of less toxic simple organic mixtures [ 14 , 32 , 33 , 34 ]. However, in the mentioned publications, only different model compounds (analytical degree) or actual wastewater were looked at, with no detection of contaminants before and following treatment.…”
Section: Introductionmentioning
confidence: 99%